Investing in Adult Continuing Education as a Strategy for Rural Economic Development - Allen B. Moore; Kevin McNamara (Journal of Research in Rural Education, 1990)
This paper presents a conceptualization of how adult education can be a strategy for rural economic development. Adult Education has the potential for improving the quality of life for individuals living in rural areas by expanding their access to income and employment opportunities. Adult education is a continuing process where adults, who perform multiple social roles, participate in organized learning activities to improve their human resource skills or their human capital assets. Economists view participation in adult education as an investment in the capital assets of the individual. These investments may be viewed as existing levels of education (stock) or what is under development (flow). Benefits from investment in adult education accrue to both the individual and community. Rural economic development is linked to the existence or improvement ofphysical, material, capital, and human resources of an area.